Implementation of sustainable economic model of a state with generation of companies (2016)
In this paper a new economic model will be shown, in which the state change its way of getting resources without impoverishing the people by creating new taxes or increasing more the existing ones, but congregating entrepreneurs and unions creating a union which will bring gains for all parties proportionate, as now the country is in crisis. This model will attack inequality in the distribution of profits generated by the primary resources of the country, which in turn generates poverty and overcrowding in cities. All this will be achieved by unifying the state, entrepreneurs, existing trade association and unionize producers of different products that not belong to a union, giving certain benefits to entrepreneurs and unions, giving to understand to the state that it is possible to exit of the crisis which is going through.